Greatest hits [compact disc] (Warner Bros. Records, 2003)
From Higher Ground to the new hit Fortune Faded, this collection spans 15 years of the Red Hot Chili Peppers best. The band's mix of punk rock and funk can be heard throughout this entire collection.